Acceptability and feasibility of acceptance and commitment therapy for improving outcomes in hematopoietic stem cell transplant - Rhonda M. Merwin; Patrick J. Smith; J.A. Riley; Jordan Infield; Christine O’Connell; Dorothy Mayo; Ashley A. Moskovich; Lauren Hill; Hilary Winthrop; Amy Bush; Ernaya Johnson; Francesca Scheiber; et al. (PLoS ONE, 2025)
Introduction: Allogeneic hematopoietic stem cell transplant (HCT) has the potential to cure patients with hematologic malignancies, but treatment-related morbidity and mortality is high. Transplant outcomes are optimized by patients maintaining physical activity. The aim of the current study was to examine whether a brief Acceptance and Commitment Therapy (ACT) intervention is acceptable to HCT patients and caregivers and helps patients engage in healthy behavior despite physical and emotional discomfort. Methods: Patients ≥ 18 years of age who were undergoing allogenic HCT for any cancer or non-cancer illness and their caregivers were invited to complete six ACT sessions between transplant day − 30 and day + 90. Multiple small cohorts of n = 3 dyads were enrolled, and the protocol content was iterated after each cohort to reflect the experiences and breadth of concerns of individuals undergoing HCT. Acceptability was indexed by session completion rates and acceptability surveys. Pre-post 6-minute walk distance was collected as an index of physical function as part of standard care. Results: Sixteen HCT dyads enrolled in the study; 12 continued to treatment. Most participants completed all assigned sessions. Participants perceived ACT to be helpful and 70% (5 of 7) of the patients with pre-post 6-minute walk test data showed improvement. Conclusion: ACT is an acceptable and potentially useful intervention for individuals undergoing HCT. Additional controlled studies are warranted.